2023
DOI: 10.1039/d3ay01182h
|View full text |Cite
|
Sign up to set email alerts
|

Development of indirect competitive ELISA and CLEIA for quantitative analysis of melatonin in health products

Longjiang Wu,
Murtala Isah Bindawa,
Siran Zhang
et al.

Abstract: Melatonin (MT), as a hormone regulating the rhythm of sleep, is widely used in health products. However, illicit and excessive use of MT might cause undesirable effects. Therefore, it is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Chemical structure and detection methods of AAI: (A) Structure representation of AAI within the Aristolochia genus. (B) The detection ranges of previously developed methods for detecting AAI. Competition inhibition curve (I) and standard curve (II) of ic-ELISA (C) and dc-QD-FLISA (D) for AAI detection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical structure and detection methods of AAI: (A) Structure representation of AAI within the Aristolochia genus. (B) The detection ranges of previously developed methods for detecting AAI. Competition inhibition curve (I) and standard curve (II) of ic-ELISA (C) and dc-QD-FLISA (D) for AAI detection.…”
mentioning
confidence: 99%
“…The development of the ic-ELISA and dc-QD-FLISA followed established protocols briefed in the Supporting Information. ,, Subsequently, spike recovery experiments were conducted. In the context of the developed ic-ELISA, it was observed that the average recoveries for AAI in herbal medicines and traditional Chinese medicines consistently fell within the range from 85.7% to 111.89%.…”
mentioning
confidence: 99%